The Changing View of Abortion: A Study of Friedrich Wolf's Cyankali and Arnold Zweig's Junge Frau von 1914 - Sabine Schroeder-Krassnow (Studies in 20th & 21st Century Literature, 1979)
With the end of the nineteenth century, women start becoming more independent, demanding more rights, making a place for themselves in society. The docile woman who is seduced by the socially higher male and in desperation commits infanticide begins to fade from literature. At the same time a new woman with a fresh vitality emerges and deals with the old problem of pregnancy and abortion. Two works which treat this type of woman are examined and the parallels as well as the differences between the portrayal are established. Although the heroines in Wolf's play and Zweig's novel come from different social backgrounds, they encounter almost identical problems in trying to have an abortion. Zweig's novel is more detailed in its account of the abortion than the play, and although it was written only two years after Wolf's play, Zweig takes the problem of the modern woman a big step further by not letting his heroine die as a result of the abortion.
Keywords: nineteenth century; women; independent; infanticide; pregnancy; abortion; Wolf; play; Zweig; modern woman; novel